An investigation into the impact of conflict and non-conflict related traumas in the north of Ireland on PTSD and aggression - Caldwell, Frances (2017)
Background: The impact of trauma on mental health is well established, but the specific effects of trauma relating to war or conflict and how this manifests behaviourally is less well understood. This research sought to investigate the impact of conflict and non-conflict related experiences on mental health outcomes and intra-familial aggression in the context of the north of Ireland following the thirty year Troubles conflict. This research is of value as previous research in this area suggests that traumatic symptoms and disproportionately high suicide rates are a current trans-generational issue in the north of Ireland. A better understanding of the impact of particular traumas is important in developing effective treatment facilities for addressing these widespread issues which could improve quality of life across those directly and indirectly affected by conflict.